2015
DOI: 10.1186/s12879-015-0999-4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of infection control in health facilities in Arua district, Uganda: a cross-sectional study

Abstract: BackgroundAt least 1.4 million people are affected globally by nosocomial infections at any one time, the vast majority of these occurring in low-income countries. Most of these infections can be prevented by adopting inexpensive infection prevention and control measures such as hand washing. We assessed the implementation of infection control in health facilities and determined predictors of hand washing among healthcare workers (HCWs) in Arua district, Uganda.MethodsWe interviewed 202 HCWs that included 186 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
5
28
1
Order By: Relevance
“…Interventions tried in other countries to increase the compliance of healthcare workers with SPs include but not limited to in-service training on SPs beyond ordinary level [ 23 ], preservice training by inclusion of SPs in educational curricula [ 24 ], and availability of personal protective equipment [ 6 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions tried in other countries to increase the compliance of healthcare workers with SPs include but not limited to in-service training on SPs beyond ordinary level [ 23 ], preservice training by inclusion of SPs in educational curricula [ 24 ], and availability of personal protective equipment [ 6 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…2 HAIs cost thousands of lives each year, yet most infections can be prevented with inexpensive Standard Precaution (SP) practices such as hand hygiene and wearing gloves. 3 According to the World Health Organization, the practice of SPs includes the basic principles of infection control such as handwashing and using personal protective equipment such as gloves, masks, gowns, and eyewear to prevent contact with potentially infectious materials, as well as safe handling of sharps. 4 Experts at the Centers for Disease Control and Prevention have reported that the recent occurrence of highly infectious diseases like severe acute respiratory syndrome, Middle-East respiratory syndrome, and Ebola virus disease have made the knowledge, practice, and enforcement of SPs more important than ever.…”
mentioning
confidence: 99%
“…Healthcare workers can contaminate hands and medical devices with even a single contact with the patient or his/her immediate surroundings. Contaminant transfer to other patients and healthcare workers is common if hand hygiene is inadequate or not performed [82]. Innumerable challenges to improving hand hygiene in resource-limited settings have been identified, but reasons vary from location to location [83].…”
Section: Hygienementioning
confidence: 99%
“…Despite the clear evidence that the use of alcohol-based hand rub solutions reduces the risk of infection transmission [83], commercial alcohol-based hand rubs are often unavailable in resource-limited settings [82]. A study from Egypt suggests that locally prepared alcohol-based hand rubs are similarly effective to commercial products [89], so local preparation of these products may be feasible and potentially more affordable than purchase of foreign-made products, with recipes readily available [125].…”
Section: Hygienementioning
confidence: 99%